2001
DOI: 10.1074/jbc.m100305200
|View full text |Cite
|
Sign up to set email alerts
|

C-terminal Splice Variants of the Mouse µ-Opioid Receptor Differ in Morphine-induced Internalization and Receptor Resensitization

Abstract: The main analgesic effects of the opioid alkaloid morphine are mediated by the -opioid receptor. In contrast to endogenous opioid peptides, morphine activates the -opioid receptor without causing its rapid endocytosis. Recently, three novel C-terminal splice variants (MOR1C, MOR1D, and MOR1E) of the mouse -opioid receptor (MOR1) have been identified. In the present study, we show that these receptors differ substantially in their agonist-selective membrane trafficking. MOR1 and MOR1C stably expressed in human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
186
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(197 citation statements)
references
References 26 publications
10
186
1
Order By: Relevance
“…Internalization can enhance desensitization by reducing functional receptors at the cellular membrane or can reduce desensitization by promoting receptor recycling to cell surface. -Opioid receptor is reported to recycle back to membrane and resensitize after internalization (27,28). Thus, the slower desensitization rate of wild type MOR could be attributed to its faster recycling, which is associated with resensitization.…”
Section: Resultsmentioning
confidence: 99%
“…Internalization can enhance desensitization by reducing functional receptors at the cellular membrane or can reduce desensitization by promoting receptor recycling to cell surface. -Opioid receptor is reported to recycle back to membrane and resensitize after internalization (27,28). Thus, the slower desensitization rate of wild type MOR could be attributed to its faster recycling, which is associated with resensitization.…”
Section: Resultsmentioning
confidence: 99%
“…More specifically, segments of the carboxyl tail and specific residues contained therein have been identified for both (20,23,24) and ␦ (25) receptors as important for agonist-induced internalization. We hypothesized therefore, that the inability of the ␦ receptor to internalize when co-expressed with the receptor indicated that the relevant region of the carboxyl tail that mediated ␦ opioid receptor internalization was somehow occluded.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, numerous studies have suggested that morphine does not efficiently promote MOR regulation by GRK and arrestin. Morphine has been shown either to be unable to induce MOR phosphorylation (29,30) or to induce less phosphorylation of MOR compared with higher efficacy agonists such as DAMGO (31,32). Additionally, morphine was unable to promote internalization of MOR in heterologous cell systems (7), although more recently morphine was shown to produce internalization in striatal neurons when MOR-and GFP-tagged arrestin were overexpressed (18).…”
Section: Discussionmentioning
confidence: 99%